The influence of Alexithymia in the processes of attention: detection of emotional facial expressions - Vitorino, Patrícia (2014)
Alexithymia is characterized by difficulties in emotional processing and facial expression recognition, essential processes in interpersonal relationship. In this study we intended to evaluate if facial expressions processing in individuals with high levels of alexithymia, especially negative emotional expressions (anger, disgust), is distinguished from the processing done by individuals with low levels of alexithymia. The participants (67 women) performed a visual search task in which sets of emotional facial expressions (happyness, anger and disgust) were presented among neutral facial expressions. The participants’ task was to detect the presence or absence of these emotional facial expressions as quickly and accurately as possible. The results revealed no significant differences between the target groups. However, there was a differential processing of the emotional facial expressions according to the face gender. The negative emotional expressions on faces of men were promptly detected. On the other hand, the processing of faces of women who expressed anger led to a greater proportion of errors. The evolutionary assumptions associated with the processing of negative emotions, which the literature in the relationship between emotion and attention indicates as being an adaptive process in the general population, may explain the absence of significant effects between the groups with high and low levels of alexithymia.